Total synthesis of mambalgin‐1/2/3 by two‐segment hydrazide‐based native chemical ligation. (15th March 2016) - Lan, Huan; Wu, Kun; Zheng, Yong; Pan, Man; Huang, Yi‐Chao; Gao, Shuai; Zheng, Qing‐Yun; Zheng, Ji‐Shen; Li, Yi‐Ming; Xiao, Bailong; Liu, Lei
Abstract : Mambalgins are a class of 57‐residue polypeptide toxins isolated from the venom of the African mamba. They exhibit potent analgesic effects by inhibiting the acid‐sensing ion channels. Classified as members of the family of three‐finger toxins, mambalgins contain four pairs of disulfide bridges that help to stabilize the three‐finger scaffold. Here, we report the chemical synthesis of functional mambalgin‐1/2/3 by using one‐step two‐segment hydrazide‐based native chemical ligation. The two‐segment ligation approach reported here may enable efficient production of mambalgin toxins. These synthetic mambalgins are useful compounds for development of diagnostic or therapeutic reagents. Copyright © 2016 European Peptide Society and John Wiley & Sons, Ltd. Abstract : Here we report the successful chemical synthesis of mambalgin‐1/2/3 by using one‐step two‐segment hydrazide‐based chemical ligation combined with the microwave‐assisted solid‐phase peptide synthesis, which is a simpler and faster protocol compared to previous three‐segment ligation strategies.